Evaluating the impact of various biofertilizer sources on growth and yield attributes of spring rice (Oryza sativa L.) in Eastern Terai of Nepal - Mehata, Dipesh Kumar (2023)
A field study was conducted at a farmer’s field in Ratuwamai, Morang, from February 2023 to June 2023 to assess the impact of various bio-fertilizer sources on the growth and yield characteristics of rice. The experiment followed a randomized complete block design (RCBD) with three replications and seven treatments. The treatments included: T1: Recommended NPK dose (100:30:30 kg/ha), T2: Farmyard manure (FYM) (12 t/ha), T3: Goat manure (8 t/ha), T4: Mycorrhiza (11.25 kg/ha), T5: Organic manure (11.25 kg/ha), T6: Mustard seed cake (3.75 t/ha), and T7: Control (no fertilizer). Our investigation explored the significant effects of these treatments on the growth and yield-contributing attributes of the Chaite-4 rice variety. Results indicated that T1 (7021.47 kg/ha) and T2 (6681.70 kg/ha) exhibited the highest grain yield, followed by T3 (5128.35 kg/ha), T2 (4482.78 kg/ha), T5 (4335.79 kg/ha), T4 (4253.80 kg/ha), with T7 showing the lowest yield (3971.64 kg/ha). The maximum straw yield was observed in T1 (11037.50 kg/ha) and T6 (10644.16 kg/ha), while the control (T7) had the lowest (7681.66 kg/ha). Additionally, parameters such as plant height, number of tillers per hill, effective tillers per hill, panicle length, panicle weight, 1000-grain weight, grains per panicle, and SPAD value were highest in T1 and T6, and lowest in T7. Furthermore, the biofertilizers with the greatest benefit-to-cost ratios were organic manure and mycorrhiza (2.0 and 1.9, respectively), while goat manure showed an average ratio (1.6), indicating their cost-effectiveness. These findings demonstrate that the application of these biofertilizers enhances rice crop development and output, leading to substantial returns on investment.